2018
DOI: 10.1016/j.neurobiolaging.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

“Lipid raft aging” in the human frontal cortex during nonpathological aging: gender influences and potential implications in Alzheimer's disease

Abstract: Lipid rafts are highly dynamic membrane domains featured by distinctive biochemical composition and physicochemical properties compared with the surrounding plasma membrane. These microstructures are associated not only with cellular signaling and communication in normal nerve cells but also with pathological processing of amyloid precursor protein in Alzheimer's disease. Using lipid rafts isolated from human frontal cortex in nondemented subjects aging 24 to 85 years, we demonstrate here that lipid structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 48 publications
6
52
0
Order By: Relevance
“…In particular, aged LRs exhibit altered raft lipidomic profiles and physicochemical properties that affect protein associations and may contribute to the cell-cell propagation of toxic α-syn aggregates (Marin et al, 2017; Rodriguez et al, 2018). In this order of ideas, we have demonstrated in the human frontal cortex of both incidental and advanced PD subjects, the presence of lipid changes in LRs that correlate with the progression of the disease (Fabelo et al, 2011; Diaz et al, 2018). Noticeably, even in asymptomatic incidental PD (iPD) brains, there was a detectable reduction of AA and DHA, in parallel with an increase of saturated fatty acids (SFA, 16:0 and 18:0).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…In particular, aged LRs exhibit altered raft lipidomic profiles and physicochemical properties that affect protein associations and may contribute to the cell-cell propagation of toxic α-syn aggregates (Marin et al, 2017; Rodriguez et al, 2018). In this order of ideas, we have demonstrated in the human frontal cortex of both incidental and advanced PD subjects, the presence of lipid changes in LRs that correlate with the progression of the disease (Fabelo et al, 2011; Diaz et al, 2018). Noticeably, even in asymptomatic incidental PD (iPD) brains, there was a detectable reduction of AA and DHA, in parallel with an increase of saturated fatty acids (SFA, 16:0 and 18:0).…”
Section: Introductionmentioning
confidence: 86%
“…Our previous work has shown that LRs exhibit pathological modifications with the progression of aging that are exacerbated in age-related neuropathologies (Marin et al, 2016, 2017; Canerina-Amaro et al, 2017; Diaz et al, 2018; Marin and Diaz, 2018). In particular, aged LRs exhibit altered raft lipidomic profiles and physicochemical properties that affect protein associations and may contribute to the cell-cell propagation of toxic α-syn aggregates (Marin et al, 2017; Rodriguez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other example is work with nerve injury and persistent inflammation, where TLR4 signaling has been reported to play a pivotal role in males in mediating the persistent pain state after nerve injury (7) and inflammation (8). With regard to aging, recent work has revealed that cortical lipid rafts are modified by aging in a sex-dependent fashion being more pronounced in women than in men (134). The effect of such sex-dependent changes in nociceptive processing remain to be assessed.…”
Section: Other Intervening Variables: Sexual Dimorphism and Agingmentioning
confidence: 99%
“…This is partly, due to different reproduction, hormonal and growth needs of both sexes. Furthermore, several studies have demonstrated that there are clear sex associated differences in lipid profile with age [31][32][33][34][35] . However, further detailed studies are required to enhance our understanding of the role of lipids in regulation of lifespan between sexes.…”
mentioning
confidence: 99%